Childhood Emotional Maltreatment and Romantic Relationships: The Role of Compassionate Goals - Sun, Lining; Canevello, Amy; Lewis, Kathrine A.; Li, Jiqiang; Crocker, Jennifer (Frontiers in Psychology, 2021)
Past research indicates that childhood emotional maltreatment (CEM) undermines the quality of adult romantic relationships by fostering negative characteristics in survivors. Two longitudinal studies investigated the hypothesis that decreased compassionate goals toward partners over time explain the association between CEM and declining relationship quality. In Study 1, CEM predicted decreased compassionate goals over time, which in turn predicted decreased relationship quality in individuals in romantic relationships. Study 2 replicated this effect in romantically involved couples and showed that partners’ high compassionate goals attenuated the decline in compassionate goals associated with reported CEM. These results point to the importance of examining how CEM may affect positive relationship processes and the protective roles of partners’ compassionate goals.